Asthma induced by enkephalin. Issue 6206 (5th January 1980) - Leslie, R D; Bellamy, D; Pyke, D A
Abstract : A total of 291 diabetics were studied to see whether an asthmatic reaction was associated with facial flushing induced by chlorpropamide and alcohol. Of these patients, 191 reported facial flushing, of whom 12 reported breathlessness as well. Of these 12, five also described wheezing, and respiratory function tests showed them to have asthma. Three of these five patients underwent further tests, which showed that the asthmatic reaction could be prevented by giving disodium cromoglycate and the specific opiate antagonist naloxone. One patient developed wheezing when given an enkephalin analogue with opiate-like activity. Asthma induced by chlorpropamide and alcohol was concluded to be mediated by endogenous peptides with opiate-like activity such as enkephalin.